Low power and high performance arithmetic circuit - Hua, Ziyun. (2009)
This report presents several classes of XOR and Multiplexor based adders, 4-2 and 5-2 compressors are surveyed based on their delay, power and number of transistors for single unit block. The adders studied including the ripple carry adder, Carry select adder (CSA), Self Energy Recovery Full Adder and G-/P- XNOR based Full Adder. For the compressors, 7 XOR and 5 MUX modules forms nine 4-2 compressors and nine 5-2 compressors respectively. The delay, power will be tested under the worst case delay conditions. And the supply power ranged from 0.6 V to 3.3 V is examined to see the relationship to the performance. In the end, the transistors of each design will be countered.